The Effect of Elevated Temperature on Tensile Properties of Unidirectional Carbon Fiber Reinforced Polymer (CFRP) Composites - Nithyananda Dhanik, Kini M Vijaya, Padmaraj N H (International Journal of Advanced Science and Technology, 2020)
The composite structures are often exposed to elevated temperatures, which adversely affects the mechanical properties during the service life. The present study investigates the effect of elevated temperature on tensile properties of unidirectional carbon fiber reinforced 3 and 4 layered laminates. Carbon prepreg based specimens were manufactured using autoclave assisted-vacuum bagging technology. The cured composite specimens were then subjected to tensile tests at ambient and elevated temperatures of 50, 75, and 100°C to elaborate on the mechanical characterization of the specimens. The stress, strain, and Young's modulus of the specimens were estimated to understand the degradation of the mechanical properties of the specimens with increasing temperatures.  Specimens of 3 and 4 layered CFRP composite which failed at ambient conditions were considered for failure surface analysis by a Scanning Electron Microscope.